The impact of Chinese university music teachers’ teaching beliefs on creative teaching behaviors: the mediating role of technological acceptance - Zhang, Rong; Wang, Hsuan-Po (Frontiers in Education, 2024)
This study focuses on college teachers in the Ningxia Hui Autonomous Region of China, aiming to explore the relationships among teaching beliefs, creative teaching behaviors, and technology acceptance. The research adopts a questionnaire survey method, using scales for teaching beliefs, creative teaching behaviors, and technology acceptance to conduct online surveys of college teachers in the Ningxia Hui Autonomous Region of China. Convenience sampling is employed during the survey. The study mainly verifies the theoretical model proposed by using statistical analysis software such as SPSS and AMOS. The results reveal that teaching beliefs of college teachers in the Ningxia Hui Autonomous Region of China positively predict creative teaching behaviors; teaching beliefs positively predict technology acceptance; technology acceptance positively predicts creative teaching behaviors; and technology acceptance has a significant mediating effect between teaching beliefs and creative teaching behaviors.